1998
DOI: 10.1183/09031936.98.11020361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary intake of omega-3 and omega-6 fatty acids on severity of asthma in children

Abstract: We assessed the clinical and biochemical effects in asthmatic children of fish oil supplementation and a diet that increases omega-3 and reduces omega-6 fatty acids. Thirty nine asthmatic children aged 8-12 yrs participated in a double-blind, randomized, controlled trial for 6 months during which they received fish oil capsules plus canola oil and margarine (omega-3 group) or safflower oil capsules plus sunflower oil and margarine (omega-6 group). Plasma fatty acids, stimulated tumour necrosis factor alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
3
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 18 publications
3
123
3
3
Order By: Relevance
“…A European ecological study found no associations between PUFA consumption and sensitisation, but supported the hypothesis that a high intake of monounsaturated fatty acids (MUFA) may lead to the development of atopic disease [10]. Epidemiological studies conducted in children revealed an inverse association between high fish consumption, which provides long chain omega-3 fatty acids, and the prevalence of asthma and bronchial hyperresponsiveness, and inferred that a decreased omega-6 to omega-3 ratio attenuates the inflammatory immune reaction [8][9][10][11]. Evidence from a recent clinical study in neonates indicates that altered membrane PUFA profiles during gestation may influence immunological function [12].…”
mentioning
confidence: 84%
“…A European ecological study found no associations between PUFA consumption and sensitisation, but supported the hypothesis that a high intake of monounsaturated fatty acids (MUFA) may lead to the development of atopic disease [10]. Epidemiological studies conducted in children revealed an inverse association between high fish consumption, which provides long chain omega-3 fatty acids, and the prevalence of asthma and bronchial hyperresponsiveness, and inferred that a decreased omega-6 to omega-3 ratio attenuates the inflammatory immune reaction [8][9][10][11]. Evidence from a recent clinical study in neonates indicates that altered membrane PUFA profiles during gestation may influence immunological function [12].…”
mentioning
confidence: 84%
“…(1998) (115) RCT, double-blind, parallel design Comparison of diet high in n-6 fatty acids and diet high in n-3 fatty acids 2-week run-in period followed by 6-month intervention period (118) RCT, cross-over design, double-blind, placebocontrolled Comparison of n-3 fatty acid supplementation with placebo supplementation 10-week intervention period, 6-week washout and then 10-week cross-over intervention baseline; however, the magnitude of change between groups was not significant (115) . PEF has been reported in some studies as a marker for lung function.…”
Section: Evidence From N-3 Intervention Trials In Asthmamentioning
confidence: 99%
“…Most of these studies enrolled a small number of asthmatic patients randomly assigned to receive a high dose of n-3 PUFA (3-4 g of EPA) for a short time-period (6-10 weeks); results were inconsistent. Studies with longer intervention periods, from 6 months to 1 yr, also led to inconsistent results with some studies showing improvement in lung function [100,101] or inflammatory markers [101][102][103], or no effect [104]. The dosage and duration of n-3 PUFA supplementation, and the type of asthmatic patients differed between studies and may explain the discrepancy between these studies [12,34].…”
Section: Inflammatory Responsementioning
confidence: 99%